2020
DOI: 10.1136/ijgc-2020-001658
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcomes after delayed cytoreduction surgery following neoadjuvant chemotherapy in advanced epithelial ovarian cancer

Abstract: ObjectiveInterval cytoreduction following neoadjuvant chemotherapy is a well-recognized treatment alternative to primary debulking surgery in the treatment of advanced epithelial ovarian cancer where patient and/or disease factors prevent complete macroscopic disease resection to be achieved. More recently, the strain of the global COVID-19 pandemic on hospital resources has forced many units to alter the timing of interval surgery and extend the number of neoadjuvant chemotherapy cycles. In order to support t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…In the NACT group, the median OS in our study was 52.8 months, in line with the findings of Luyckx (54 months), and is one of the highest reported values [20,[31][32][33]35,[37][38][39][40]. Despite our low PDS rate (38%), our median OS and PFS were 65.5 months and 21.9 months, respectively, for the whole cohort, which is concordant with data in literature [40,41].…”
Section: Discussionsupporting
confidence: 92%
“…In the NACT group, the median OS in our study was 52.8 months, in line with the findings of Luyckx (54 months), and is one of the highest reported values [20,[31][32][33]35,[37][38][39][40]. Despite our low PDS rate (38%), our median OS and PFS were 65.5 months and 21.9 months, respectively, for the whole cohort, which is concordant with data in literature [40,41].…”
Section: Discussionsupporting
confidence: 92%
“…As a practice recommended by the National Comprehensive Cancer Center (NCCN), complete cytoreduction to no gross residual disease is a vital factor affecting the progression-free and overall survival of ovarian cancer patients at stage IV ( 32 , 33 ). Another study also indicated that complete surgical cytoreduction had the best survival benefit in advanced epithelial ovarian cancer patients ( 34 ). Balkhy et al indicated that surgery was the cornerstone of treatment for most stages of non-epithelial ovarian cancers, which might correlate with the prognosis of those patients ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of survival outcomes and delayed debulking surgery following NACT concluded that delays between NACT and IDS were not associated with worse OS after adjusting for known confounders. However, debulking surgery was necessary in order to maintain improved survival with the caveat that it was undertaken after at least three cycles of NACT [ 41 42 ].…”
Section: Upfront Surgery Versus Neoadjuvant Chemotherapy: Brawn Versus Biologymentioning
confidence: 99%